Pharmacokinetics and pharmacodynamics of ‘old’ polymyxins: what is new? - Bergen, Phillip J. (2012)
‘Old’ colistin and polymyxin B are increasingly used as last-line therapy against multidrug-resistant Gram-negative bacteria Pseudomonas aeruginosa, Acinetobacter baumannii and Klebsiella pneumoniae. For intravenous administration, colistin is dosed as its inactive prodrug colistin methanesulfonate (sodium), while polymyxin B is used as its sulfate (active antibacterial). Over the last decade significant progress has been made in understanding their chemistry, pharmacokinetics (PK) and pharmacodynamics (PD). The first scientifically based dosing suggestions are now available for colistin methanesulfonate to generate a desired target steady-state plasma concentration of formed colistin in various categories of critically-ill patients. As simply increasing polymyxin dosage regimens is not an option for optimizing their PK/PD due to nephrotoxicity, combination therapy with other antibiotics has great potential to maximize the efficacy of polymyxins while minimizing emergence of resistance. We must pursue rational approaches to the use of polymyxins and other existing antibiotics through the application of PK/PD principles.